KATA MAJEMUK VERBA BAHASA JEPANG - Elizabeth Ika Hesti Aprilia Nindia Rini (KIRYOKU, 2018)
(Title: Japanese verb compound words) As an agglutinative language, the formation of the word in Japanese is done morphologically. The word joins Japanese consists of compound words (複合 語), words reduplication (畳 語), and derivative words (派生 語). This study aims to describe the structure and relationship of the meaning of verb compound words. The method used is the descriptive method. As a result of the study, it was found that verb compound words have patterns (N + V), (V + V), (A + V), and (AD + V). The relation of the meaning of the pattern (N + V) is A subject B, object B, and A tool or material B. The relation of the meaning of the pattern (V + V) is the first/second element to lose its substantive meaning, the first and second elements cannot be described again, parallel relations (synonyms and antonyms). There is not much pattern (A + V) found. The pattern (AD + V) expresses the description of the situation with onomatopoeia.